Credit Risk Management in Sharia Banking - mirda, saprian (Universitas Serang Raya, 2024)
Credit risk management in sharia banking is a very important aspect to maintain the stability and sustainability of the operations of sharia financial institutions. Credit risk arises when debtors fail to fulfill their obligations, which can have a negative impact on the bank's financial health. In order to manage this risk, Islamic banks use strategies such as observation, measurement, supervision and risk control. These steps include an internal control system, risk management policies and supervision by the board of commissioners are part of this action. Islamic banks also face operational, legal, market, strategic, reputation, compliance, investment and return risks. Implementing efficient risk management strategies enables Islamic banks to mitigate potential losses and increase operational efficiency, thereby maintaining customer trust and ensuring sustainable long-term growth. This journal aims to analyze challenges and strategies in credit risk management in Islamic banking, as well as provide recommendations for increase the effectiveness of risk management. By understanding the characteristics of credit risk and applying sharia principles, sharia banks can reduce potential losses and increase customer confidence